The impact of anti-infective therapy on patients undergoing warfarin treatment - Fu, Linlin; Yao, Huimin; Xu, Wei; Li, Li; Wang, Baoyan (The Journal of Infection in Developing Countries, 2024)
Introduction: The combination of antibiotics and warfarin is used frequently in clinical practice. However, the impact of this combination on the anticoagulant efficacy of warfarin remains uncertain, posing challenges to clinical decision-making. This study aimed to evaluate the influence of various antibiotics on the international normalized ratio (INR) values in hospitalized patients who were concurrently administered warfarin. Methodology: This retrospective cohort study enrolled patients who received concomitant warfarin and antibiotic therapy at the Nanjing Drum Tower Hospital, between January 2013 and December 2022. The patients were categorized into 8 groups based on the type of antibiotics they were received. The demographic characteristics were recorded, and the clinical outcomes were focused on changes in INR values after combining antibiotics in warfarin users. Results: A total of 623 patients were enrolled in this study. Based on analysis of covariance (ANCOVA), the maximum INR values of the combinations were as follows: 2.72 for oxazolidinones, 2.86 for β-lactams, 2.86 for carbapenems, 2.91 for glycopeptides, 2.91 for macrolides, 3.77 for quinolones, 4.13 for sulfonamides, and 4.37 for antifungal agents. Pairwise comparisons revealed that quinolones, sulfonamides, and antifungal agents manifested the most substantial elevation in INR values when co-administered with warfarin. β-lactams, glycopeptides, oxazolidinones, macrolides, and carbapenems demonstrated a comparatively weaker impact on INR values. Conclusions: Co-administration of warfarin with antibiotics led to an elevation in INR values in patients. Quinolones, sulfonamides, and antifungal agents had the most pronounced impact.